Di[(R)-2-ethylhexyl] Phthalate, a Bioactive Metabolite First Isolated from Three Different Bacillus Species, and its Synthesis - Castro, Miriam; Jiménez, Jacqueline; Ortiz, Aurelio; Sansinenea, Estibaliz (Letters in Organic Chemistry, 2020)
Di(2-ethylhexyl) phthalate (DEHP) is the most common phthalate ester, which has been used as a plasticizer for the production of numerous polymers, particularly polyvinyl chloride (PVC). Many other groups have synthesized meso-DEHP indicating interest in this molecule, but we are the first to synthesize enantiomerically pure di[(R)-2-ethylhexyl] phthalate. We report herein, for the first time, the isolation - from the cultures of Bacillus thuringiensis, B. subtilis, and B. velezensis strains - of di[(R)-2-ethylhexyl] phthalate, enantiomerically pure and in good yields: its biological activity against bacteria and fungi was probed and for the first time its synthesis was done.
Keywords: Di(2-ethylhexyl) phthalate